Sekolah Swasta: SD Pius Payakumbuh Yayasan Prayoga (1962-1990) - Muthia Zikrah; Abdul Salam (Jurusan Sejarah FIS UNP, 2023)
This thesis is a study of the history of educational institutions, by looking at the components of education that build a school. This research focuses more on: How was the development of the Pius Payakumbuh Elementary School Prayoga Foundation, from 1962-1990. Which later in looking at this development, this research focuses more on the development of the Pius Payakumbuh Elementary School seen from teachers, students, curriculum and facilities and infrastructure from 1962-1990. This study aims to determine the development of the Pius Payakumbuh Elementary School Prayoga Foundation (1962-1990). To achieve this goal, a historical research method which consists of four stages is used. The first stage of heuristics is to collect data, both primary and secondary data. Primary data in the form of documents related to Pius Payakumbuh Elementary School and oral sources derived from interviews with informants by preparing pre-designed questions. The second stage of source criticism, namely testing and selection of the collected data to see the level of authenticity or authenticity of the data carried out through external criticism and testing the informants contained in the internal criticism. The third stage is data analysis and interpretation, namely classifying and sorting and assembling the criticized data so that it can be reconstructed in the form of stories. The fourth stage of historiography, namely the presentation of research results in the form of a thesis. The results showed that Pius Payakumbuh Elementary School was started by Pastor Spinabelli s.x and Pastor Mario s.x in 1953. At first the Pius school was under the care of the church which was the only church in Payakumbuh, namely the Catholic Church of St. Fidelis a Sigmarinda. After the establishment of the Prayoga Foundation on March 26, 1962, the management of schools under the care of the church in West Sumatra was handed over to the Prayoga Foundation, including Pius Payakumbuh Elementary School to coordinate Catholic schools in the West Sumatra region. The number of students grew so rapidly that in the 1980s the building was extended to the rear. Although it is classified as a Catholic school, the students and teachers of Pius Payakumbuh Elementary School are ethnically diverse and the majority are Muslim, but the social relations between them remain harmonious.